Effect of Pumpkin Soygurt on Microbiota Balance in Diabetes Mellitus Model Rats - Annisa Avelia; Didik Gunawan Tamtomo; Yulia Sari (Global Health Science Group, 2023)
Microbiota imbalance in the gastrointestinal tract causes low-grade systemic inflammation, which triggers metabolic changes and insulin resistance to become diabetes mellitus. This condition can be controlled through synbiotic supplementation through pumpkin soygurt containing lactic acid bacteria and polysaccharides. This study aimed to analyze the effect of complementary therapy using pumpkin soygurt and metformin on the abundance of lactic acid bacteria and Escherichia coli in a rat model of diabetes mellitus. The research design is experimental with a post-test only. Male Wistar rats were divided into six groups; healthy rats (KS), DM rats (K-), DM+metformin rats (K+), DM+metformin+1 mL pumpkin soygurt rats (P1), DM+metformin+ 1.5 mL pumpkin soygurt rats (P2), DM + metformin + 2 mL of pumpkin soygurt (P3) rats. The test material was given for four weeks. The abundance of LAB and Escherichia coli was analyzed using a sample of the contents of the cecum with the method total plate count. Data were analyzed using the One way ANOVA test. This study showed a dysbiosis condition on K- (BAL 6.85 CFU/mL; Escherichia coli 8.80 CFU/mL) dan K+ (BAL 4,99 CFU/ml; Escherichia coli 7.67 CFU/mL). In the treatment group, eubiotics were maintained, with the best conditions in group P2 with a BAL of 7.46 CFU/mL and Escherichia coli 4,62 CFU/mL. The combination of pumpkin soygurt and metformin can maintain the balance of the gastrointestinal microbiota in DM model rats, especially lactic acid bacteria and Escherichia coli.